Penerapan Aplikasi Android Terintegrasi Firebase dalam Sistem IoT untuk Monitoring Kolam Lele Berbasis Realtime Database dan Firestore dengan Pengujian Blackbox - Wirawan, I Made Aditya; Astawa, I Komang Alit; Wijaya, Putu Ananta Sastra; Agung, I Gusti Agung Putu Raka; Shandyasa, I Wayan (Universitas Pahlawan Tuanku Tambusai, 2025)
Catfish farming faces challenges in consistently monitoring pond conditions. This study aims to design and develop an Android application connected to Firebase services to support pond condition monitoring based on an Internet of Things system. The application enables users to view sensor data via a mobile interface and store observation history using two database services: Realtime Database and Firestore. The development process applied software modeling, and the system was tested using the blackbox method. The results show that the application successfully displays data, records history, and responds to user input as expected. These findings indicate that the developed system can serve as a digital solution to support integrated pond monitoring through mobile devices.